(untitled) (Iranian Journal of Kidney Diseases, 2017)
Introduction. Thymoquinone is a phytochemical compound found in the plant Nigella sativa. It has various pharmacological effects such as antioxidant and anti-apoptotic. Morphine can increase the generation of free radicals. It is mainly excreted through the kidneys and causes disturbing effects. This study was designed to evaluate protective effects of thymoquinone against morphine-induced damages to the kidneys of mice. Materials and Methods. Various doses of thymoquinone (4.5 mg/kg, 9 mg/kg, and 18 mg/kg) were intraperitoneally administered along with morphine to 48 male mice for 20 consequent days. These mice were compared with a control group with saline injection, morphine group, and groups with same doses of thymoquinone only (n = 6 in each group). Blood urea nitrogen, serum creatinine, and serum nitric oxide levels, as well kidney weight and histology were assessed after the interventions. Results. Morphine administration significantly decreased kidney weight and the number and mean diameter of the glomeruli. Increased levels of blood urea nitrogen, serum creatinine, and serum nitric oxide were also noted with morphine compared to the control group (P < .05). However, administration of thymoquinone and thymoquinone plus morphine significantly enhanced kidney weight, number and mean diameter of the glomeruli. All of the groups with thymoquinone were also associated with reduced blood urea nitrogen, serum creatinine, and serum nitric oxide levels compared to the morphine group (P < .05). Conclusions. It seems that antioxidant and anti-apoptotic effects of thymoquinone could protect of the kidneys against damage due to morphine toxicity.